Doing business in a new climate : a guide to measuring, reducing and offsetting greenhouse gas emissions - Lingl, Paul (Earthscan, 2010)
Around the world, a growing number of businesses are taking steps to reduce their climate impact by managing their greenhouse gas emissions. At the same time, these businesses are discovering that effective greenhouse gas management can enhance their brands, motivate employees, increase operational efficiencies, and save money. This guide walks readers through the key activities that make up a greenhouse gas management program, including measuring, reducing, and offsetting emissions and developing a communications strategy around the program. Throughout, case studies of over fifty leading busi.